UNCERTAINTY OF EMPLOYMENT RELATIONS AND WAGE DISCRIMINATION OF OUTSOURCED WORKERS FROM A LEGAL AND ECONOMIC PERSPECTIVE - Vinne Eunike; Catharina Dewi Wulansari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Outsourcing refers to work that is not directly related to a company's core business activities, where such work is delegated to another party or company. Generally, outsourcing can be carried out when an agreement has been signed between the labor service provider and the labor service user. However, in practice, outsourcing often leads to issues that disadvantage outsourced workers or laborers. There are companies that fail to uphold workers' rights as specified by labor laws and regulations, thus neglecting their obligations to provide all the rights of outsourced employees. As a result, even though legal provisions regulate various aspects of employment relations, they do not guarantee that companies will comply with these regulations. Problems arising from outsourcing include job insecurity and wage discrimination, both of which clearly violate the provisions set forth in labor legislation. In addition to violating the law, the issues of employment uncertainty and wage discrimination also have severe economic consequences for outsourced workers, as they struggle to achieve a decent standard of living.